2015
DOI: 10.1056/nejmoa1413687
|View full text |Cite
|
Sign up to set email alerts
|

Initial Use of Ambrisentan plus Tadalafil in Pulmonary Arterial Hypertension

Abstract: BACKGROUNDData on the effect of initial combination therapy with ambrisentan and tadalafil on long-term outcomes in patients with pulmonary arterial hypertension are scarce. METHODSIn this event-driven, double-blind study, we randomly assigned, in a 2:1:1 ratio, participants with World Health Organization functional class II or III symptoms of pulmonary arterial hypertension who had not previously received treatment to receive initial combination therapy with 10 mg of ambrisentan plus 40 mg of tadalafil (combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
917
1
52

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 985 publications
(996 citation statements)
references
References 27 publications
26
917
1
52
Order By: Relevance
“…56,57 The current clinical guidelines derive data from individual drug studies and single-agent metaanalyses. 58,59 However, the direct meta-analyses in the published literature synthesized evidence informing about either the pooled effect of drug therapy on relevant outcomes 4,7 or the effect of combination vs monotherapy as a whole without addressing the role of individual agents.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 The current clinical guidelines derive data from individual drug studies and single-agent metaanalyses. 58,59 However, the direct meta-analyses in the published literature synthesized evidence informing about either the pooled effect of drug therapy on relevant outcomes 4,7 or the effect of combination vs monotherapy as a whole without addressing the role of individual agents.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients were not well represented in PAH studies. Some of the recent clinical trials in PAH had an upper age limit of 75 years, and the average age of the enrolled patients ranged from 48 to 54 years [20,21]. Hence, most of the available data on treatment responses in older patients have been derived from registries.…”
Section: Treatment and Treatment Responsementioning
confidence: 99%
“…The results of the Ambrisentan and Tadalafil Combination Therapy in Subjects with Pulmonary Arterial Hypertension (AMBITION) study demonstrate that initial combination therapy with ambrisentan and tadalafil in newly diagnosed, treatment-naïve PAH patients with WHO Group I PAH results in a significant reduction in the risk of clinical failure events compared to initial monotherapy 21 . Specific to the CTD-PAH population, the Ambrisentan and Tadalafil Upfront Combination Thearapy in SclerodermaAssociated PAH (ATPAHSS) study demonstrated that upfront combination therapy with ambrisentan and tadalafil in treatment-naïve SSc-PAH patients significantly improved hemodynamics, RV structure and function, as well as functional status 22 .…”
Section: Discussionmentioning
confidence: 99%